Development of a multidisciplinary toolkit for the colloidal nanoparticle synthesis of copper selenophosphate, Cu3PSe4, a promising material for photovoltaics - Lee, Jennifer M., author; Prieto, Amy L., advisor; Ackerson, Chris J., committee member; Henry, Chuck S., committee member; Buchanan, Kristen S., committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.